2004
DOI: 10.1111/j.1464-410x.2004.05018.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoaugmentation gastrocystoplasty: further studies of the sheep model

Abstract: and experimental animals 6 months after surgery. The animals were then killed and the bladders evaluated for gastric flap survival and histological changes in the native bladder and augmentation segments. The results were analysed using a one-sided Student's t -test. RESULTSThe median (range) native bladder volume at leak-point pressure was 110 (40-490) mL. Intraoperative bladder volumes after completing AAGC confirmed adequate augmentation segments in all animals. The urodynamic evaluation at 6 months after A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
5
0
3
Order By: Relevance
“…Although it failed to produce any significant bladder augmentation, this technique was nonetheless highly effective in terms of sealing performance, with no leakage detected (Close et al 2004). In several cases, Close et al (2001) reported flap atrophy with scarring and contraction at necropsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it failed to produce any significant bladder augmentation, this technique was nonetheless highly effective in terms of sealing performance, with no leakage detected (Close et al 2004). In several cases, Close et al (2001) reported flap atrophy with scarring and contraction at necropsy.…”
Section: Discussionmentioning
confidence: 99%
“…We did not seek to confirm whether this also occurred in our case, but we cannot exclude the possibility. For this reason we made the flap considerably larger than the defect, bearing in mind that omentalisation of the flap itself could provide further blood supply, thereby avoiding failure and limiting adhesion formation (Close et al 2001;Close et al 2004). Further studies are needed to investigate the process of flap healing and to assess the above possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Para mejorar estos resultados, la técnica del autoaumento se ha combinado con diferentes procedimientos de refuerzo del "divertículo herniado" creado a través de la ventana realizada en el músculo detrusor, como peritoneo 72 , músculo 73 , colgajos gástricos con 74 o sin mucosa 75,76 , parches biodegradables de diferente naturaleza sembrados con células musculares autólogas 77 , etc. Una alternativa, sobre la que ya existe alguna referencia clínica en humanos, aunque con un número de casos todavía reducido 78 , sería la colocación de un injerto desepitelizado y destubularizado de intestino sobre el "divertículo" 79,80 .…”
Section: Autoaumentounclassified
“…Una alternativa, sobre la que ya existe alguna referencia clínica en humanos, aunque con un número de casos todavía reducido 78 , sería la colocación de un injerto desepitelizado y destubularizado de intestino sobre el "divertículo" 79,80 . Sin embargo, los estudios experimentales en animales utilizando injertos de intestino carentes de mucosa han mostrado resultados contradictorios en cuanto a la retracción del injerto, por lo que la efectividad de esta técnica todavía está en discusión 74,75,76,79 . 89 .…”
Section: Autoaumentounclassified
See 1 more Smart Citation